NEW METHOD TO ESTIMATE POLLUTANTS BALANCE IN MARINE WATER AREA ALLOTTED FOR EXPLORATION AND PRODUCTION OF HYDROCARBONS - G. A. Monakhova; S. K. Popov; К. I. Asaeva; N. I. Rakhimbirdiev (Юг России: экология, развитие)
Aim. Estimation of pollutants balance at the license area “Severniy” using the operational hydrodynamic model of the Caspian Sea and the data of industrial environmental monitoring.Methods. A new method was used to estimate pollutants balance at the license area based on the data of the hydrodynamic model and environmental monitoring. The indicated method was developed by Caspian Marine Scientific Research Center jointly with Hydrometeorological Centre of Russia in 2015.Results. The pollutants balance was estimated for oil products, heavy metals (copper, lead, cadmium, mercury, cobalt, iron, manganese, zinc and nickel) and the total polycyclic aromatic hydrocarbons. It was discovered that from 17 to 20 October 2014 the balance of most pollutants was negative and amounted to less than 1% of the total transport. Pollutants outflow was registered 0-5 and 5-10 m layers, and the inflow was discovered in the layers of 10-15 and 15-20 m.Conclusion. The new approach based on the modified calculation technology of water exchange and pollutants transport has performed well and will make it possible to estimate the balance and flows of pollutants passing through different areas of the Caspian Sea.